Study of Medical Hazardous And Toxic (B3) Waste Management From Health Clinic - Imam Chandra Suyuti; Suheryanto Suheryanto; Novrikasari Novrikasari (Sriwijaya Journal of Environment, 2022)
Medical waste is classified as hazardous and toxic material waste (B3) and the management of which is required to be carried by regulations established by the government. The goals of this study are to ascertain the quantity of B3 medical waste, to recognize B3 waste, and to acquire knowledge regarding the processes involved in managing B3 waste that is produced by clinical health activities. The study was conducted in one of the health clinics in Sri Katon Village, Buay Madang Timur District, East Ogan Komering Ulu Regency (East OKU), South Sumatra Province, from October to November 2021. Based on the findings of the study, it can be concluded that the health clinic's B3 waste management activities, including storage, supporting facilities, and infrastructure, comply all applicable B3 waste management laws and regulations. Waste management and storage activities commence with the identification of B3 waste, the storage procedure, and the packaging of B3 waste. Additional management activities in partnership with the third licensee